Moods Managed: Refining a Mental Health Education Game for Children and Youth in Ontario - Gardiner, Keltie (Université d'Ottawa | University of Ottawa, 2024)
There is a high need for a solution to address the mental health needs of Canadian children and youth. Due to accessibility issues, rural areas in Canada are particularly vulnerable to more mental health troubles. A useful way to promote mental health is through board games. Moods Managed is a board game designed to teach children and families about mental health, promote skills that reduce mental health issues, and foster meaning mindset. The current study involved ongoing development of the board game Moods Managed through co-creation with rural families. Through a Knowledge Translation Integrated community action approach, feedback from participants was collected and the board game was assessed regarding whether it was perceived to be doing what it was designed to do. The implications of the current study are that this board game appears to promote healthy thinking, and is a fun, accessible way to disseminate mental health information to children and families. Given the encouraging results from this project, a future study may adapt the board game based on the present co-creation findings and test the game’s validity over a longer period.
Keywords: Mental health; Play therapy; Children; Youth; Resilience